Potensi Kandungan Gas Metana sebagai Sumber Energi Alternatif di TPA Kebon Kongok - Abdullah, Taufik; Hidayat, Nur Rosman; Sholehah, Hijriati (Universitas Diponegoro, 2020)
Waste management in West Nusa Tenggara Provincial Government focuses on two main things, namely the reduction and handling and providing of TPA which is still operated with an open dumping system. Application of an open system in TPA will cause many problems, including air pollution by methane gas and the greenhouse effect. This study aims to determine the potential methane gas content of the Kebon Kongok landfill as an alternative energy source by modelling using LandGEM. The data in this study consisted of the year of the TPA operation plan and the annual data on the waste generation of TPA. The results showed that the potential content of methane gas was 12,999,633.62 m3/year, or equivalent to 14,520.88 MWh/year, in the form of gas as much as 9,966.38 Megagrams of LPG/ year. Therefore, the Kebon Kongok TPA has the potential to be used as a power plant fuelled by methane gas and facilitates electricity connections for the surrounding community because when compared to other existing renewable energy plants in the Lombok Electricity System, the capacity of 1.66 Megawatts was alreadyÂ equivalent to the power generationÂ capacity which are already operating commercially.